Titanium alloy formwork fast dismounting and assembling construction technology in low temperature environment

CN122942591APending Publication Date: 2026-10-20SHIJIAZHUANG NUAN RUCHUN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611418415.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]本申请提供了一种低温环境下快速拆装的钛合金模板防冻施工工艺,可以解决低温环境下混凝土受冻害、模板拆装困难、拆模时间延长及模板清理困难的技术问题

Benefits of technology

[0015]本申请提供了一种低温环境下快速拆装的钛合金模板防冻施工工艺,该方案通过构建包含底层防锈蚀涂层、中间相变蓄热层及表层防粘结界面层的复合防冻介质层,并结合具有低温弹性保持能力的快拆连接机构,实现了模板系统的全流程优化。具体而言,利用钛合金模板单元作为基础载体,在其工作面涂覆特定相变温度范围的复合防冻介质层,使得底层能够有效阻隔腐蚀,中间相变蓄热层能够在混凝土水化热高峰期吸收并储存热量,并在环境温度降低时释放潜热,从而缓冲界面温度波动;在此基础上,通过向模板背面输送循环热风进行主动预热,使模板工作面达到适宜温度,进而启动相变材料的蓄热功能;随后,借助弹性锁扣组件在低温下稳定的弹性形变能力与定位导向组件的精准对位功能,实现模板的快速可靠组拼;当混凝土强度发展至设定阈值时,解除锁定并利用机械振动清理残留碎渣,由此形成主动预热启动+被动蓄热维持+高效拆装清理的完整闭环。从而有效解决了低温环境下混凝土受冻害、模板拆装困难、拆模时间延长及模板清理困难的技术问题,因此避免了混凝土早期强度受损、连接件失效卡滞、施工周期冗长及模板表面损伤等情况,显著提升了低温施工的稳定性、可靠性及整体作业效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to a rapid disassembly and refrigeration process for titanium alloy formwork in low-temperature environments, belonging to the field of building formwork construction technology. The process includes: providing titanium alloy formwork units coated with a composite antifreeze medium layer consisting of a base anti-corrosion coating, an intermediate phase change heat storage layer, and a surface anti-adhesion interface layer; assembling the formwork using a quick-release connection mechanism including elastic locking components and positioning guide components; preheating the formwork with circulating hot air before pouring; regulating the interface temperature after pouring by utilizing the heat absorption and release of the phase change heat storage layer; and releasing the locking mechanism and removing the formwork when the concrete strength reaches the required level, followed by mechanical vibration cleaning. This application can effectively prevent concrete from freezing damage, solve the difficulties of disassembly and cleaning at low temperatures, and shorten the waiting time for formwork removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building formwork construction technology, specifically to a fast-assembly and disassembly process for antifreeze titanium alloy formwork in low-temperature environments. Background Technology

[0002] Formwork is an indispensable temporary support and forming component in concrete structure construction. Its performance directly determines the surface quality, dimensional accuracy, and overall construction efficiency of the concrete structure. In conventional construction projects, wooden formwork, steel formwork, and aluminum alloy formwork are the most widely used types. Each type plays a crucial role in different construction scenarios due to its lightweight, high strength, or corrosion resistance. With the continuous development of construction technology, a relatively mature technical system has been formed for material selection, structural design, and connection methods of formwork systems. Especially when facing construction needs in winter or cold regions, the industry typically adopts external auxiliary methods such as erecting insulated sheds, embedding electric heating elements for heating curing, or using steam curing to maintain the temperature environment required for concrete hardening and ensure the smooth progress of the project.

[0003] However, in actual construction under low-temperature conditions, existing technologies still face long-standing technical bottlenecks. On the one hand, due to the lack of an effective mechanism for controlling the temperature field at the interface between the formwork and concrete, concrete is highly susceptible to early freezing, leading to internal structural damage, strength loss, and reduced durability. Furthermore, traditional external heating methods often consume enormous amounts of energy and result in uneven temperature control. On the other hand, low temperatures significantly alter the mechanical properties of formwork connection components, making disassembly and assembly extremely difficult. Simultaneously, the freezing and adhesion of concrete residue to the formwork surface greatly increases the difficulty of cleaning. These problems collectively lead to macro-level challenges such as prolonged formwork removal waiting times, low formwork turnover efficiency, and difficulty in maintaining stable construction quality, severely restricting the economic efficiency and reliability of concrete structure construction in cold regions. Summary of the Invention

[0004] This application provides a rapid disassembly and assembly process for antifreeze titanium alloy formwork in low-temperature environments, which can solve the technical problems of concrete freezing damage, difficult formwork disassembly and assembly, prolonged disassembly time, and difficult formwork cleaning in low-temperature environments.

[0005] To achieve the above objectives, this application provides the following technical solution: This application provides a rapid disassembly and assembly antifreeze construction process for titanium alloy formwork in low-temperature environments, including the following steps: S1, Formwork pretreatment: Providing titanium alloy formwork units, the working surface of which is coated with a composite antifreeze medium layer. The composite antifreeze medium layer consists of a bottom anti-rust coating, an intermediate phase change heat storage layer, and a surface anti-adhesion interface layer. The phase change temperature range of the phase change heat storage layer is -5℃ to 5℃; S2, Formwork assembly: Assembling the pretreated titanium alloy formwork units using a quick-release connection mechanism. The quick-release connection mechanism includes an elastic locking component and a positioning guide component located on the side of the formwork unit. The elastic locking component maintains its elastic deformation capability at low temperatures, and the positioning guide component... S3, Anti-freeze curing: After the formwork assembly is completed and before the concrete is poured, circulating hot air is supplied to the back of the formwork to maintain the temperature of the formwork working surface at 5℃ to 15℃; After the concrete is poured, the phase change heat storage layer absorbs and stores heat under the action of concrete hydration heat, and releases heat when the ambient temperature is lower than the phase change temperature to slow down the cooling rate of the formwork-concrete interface; S4, Rapid demolding: When the concrete strength reaches more than 50% of the design strength, the locking of the elastic locking component is released, and each titanium alloy formwork unit is removed in sequence. The remaining concrete debris on the working surface of the demolded formwork is cleaned by mechanical vibration.

[0006] In one optional embodiment, the titanium alloy template unit is made of TC4 titanium alloy or TA7 titanium alloy sheet with a thickness of 4mm-10mm. The back of the template unit is provided with crisscrossing reinforcing ribs, which are integrally formed with the template unit, and the cross-section of the reinforcing ribs is T-shaped or L-shaped.

[0007] In one optional embodiment, the phase change heat storage layer is a paraffin-based phase change microcapsule coating or an inorganic salt hydrate phase change material coating, with a latent heat of phase change of 150 kJ / kg-250 kJ / kg and a coating thickness of 0.5 mm-2 mm.

[0008] In one optional embodiment, the elastic locking assembly includes a locking seat disposed on one side of the template unit, a locking hook disposed on the opposite side of an adjacent template unit, and a memory alloy spring element located between the locking seat and the locking hook, wherein the elastic modulus of the memory alloy spring element changes by no more than 15% at an ambient temperature of -20°C to 0°C.

[0009] In an optional embodiment, in step S3, the circulating hot air is delivered by a flexible air duct set on the back of the template. The flexible air duct is arranged along the splicing seam of the template unit, and air outlet holes are distributed on the surface of the air duct. The air outlet direction is towards the back of the template. The hot air temperature is 30℃-50℃ and the wind speed is 2m / s-5m / s.

[0010] In an optional embodiment, step S3 further includes: laying an insulation layer on the back of the template, the insulation layer being a closed-cell foam board or aerogel felt with a thermal conductivity not exceeding 0.035 W / (m·K), and forming an air gap with a thickness of 10 mm-30 mm between the insulation layer and the back of the template, with circulating hot air flowing in the air gap.

[0011] In one optional embodiment, the mechanical vibration cleaning in step S4 uses a high-frequency vibrator with a vibration frequency of 50Hz-200Hz, an amplitude of 0.5mm-2mm, and a vibration time of 10s-60s.

[0012] In one optional embodiment, the quick-release connection mechanism further includes a sealing strip disposed at the splice seam of the template unit. The sealing strip is made of silicone rubber or fluororubber and has a hollow cavity inside. The hollow cavity is filled with low-freezing-point antifreeze, and the freezing point of the low-freezing-point antifreeze is not higher than -30°C.

[0013] In one optional embodiment, the bottom anti-corrosion coating in step S1 is an epoxy zinc-rich coating or a polyurethane coating with a thickness of 20μm-80μm; the surface anti-adhesion interface layer is a polytetrafluoroethylene coating or a diamond-like carbon coating with a thickness of 10μm-50μm.

[0014] In an optional embodiment, the positioning guide component in step S2 includes a tapered positioning pin disposed on one side of the template unit and a tapered positioning hole disposed on the opposite side of the adjacent template unit. A flexible guide sleeve is disposed between the tapered positioning pin and the tapered positioning hole. The change in Shore hardness of the flexible guide sleeve at -20°C compared to that at room temperature does not exceed 5HA.

[0015] This application provides a rapid disassembly and assembly process for antifreeze construction of titanium alloy formwork in low-temperature environments. This solution optimizes the entire formwork system by constructing a composite antifreeze medium layer comprising a bottom anti-corrosion coating, an intermediate phase change heat storage layer, and a surface anti-adhesion interface layer, combined with a quick-release connection mechanism that maintains low-temperature elasticity. Specifically, using titanium alloy formwork units as the basic carrier, a composite antifreeze medium layer with a specific phase change temperature range is coated on its working surface. This allows the bottom layer to effectively block corrosion, while the intermediate phase change heat storage layer absorbs and stores heat during the peak of concrete hydration heat and releases latent heat when the ambient temperature decreases, thus buffering interface temperature fluctuations. Furthermore, active preheating is achieved by supplying circulating hot air to the back of the formwork, bringing the working surface to a suitable temperature and activating the heat storage function of the phase change material. Subsequently, the stable elastic deformation capability of the elastic locking components at low temperatures and the precise alignment function of the positioning guide components enable rapid and reliable assembly of the formwork. When the concrete strength reaches a set threshold, the locking is released, and mechanical vibration is used to clean residual debris, thus forming a complete closed loop of active preheating activation + passive heat storage maintenance + efficient disassembly and cleaning. This effectively solves the technical problems of concrete freezing damage, difficult formwork assembly and disassembly, prolonged formwork removal time, and difficult formwork cleaning in low-temperature environments. As a result, it avoids early strength loss of concrete, failure and jamming of connectors, lengthy construction cycle, and damage to formwork surface, and significantly improves the stability, reliability, and overall work efficiency of low-temperature construction. Attached Figure Description

[0016] Figure 1 This application provides a flowchart of a rapid assembly and disassembly process for antifreeze construction of titanium alloy formwork in low-temperature environments; Figure 2 A graph showing the temperature change of the working surface of the formwork over time in the antifreeze construction process of the titanium alloy formwork that can be quickly disassembled and assembled in a low-temperature environment, as provided in this application. Figure 3 This application provides a flowchart of the alignment and locking operation of the quick-release connection mechanism in the antifreeze construction process of titanium alloy formwork for rapid assembly and disassembly in low-temperature environments. Detailed Implementation

[0017] The present application will now be described in further detail with reference to embodiments. It is to be understood that the specific embodiments described herein are merely illustrative of the present application and are not intended to limit the scope of the application.

[0018] Example 1: like Figure 1 The diagram shown is a flow chart of a rapid disassembly and assembly process for antifreeze construction of titanium alloy formwork in low-temperature environments, provided in an embodiment of this application. The method includes: Step S1: Template pretreatment: Provide a titanium alloy template unit. The working surface of the titanium alloy template unit is coated with a composite antifreeze medium layer. The composite antifreeze medium layer consists of a bottom anti-rust coating, an intermediate phase change heat storage layer and a surface anti-adhesion interface layer. The phase change temperature range of the phase change heat storage layer is -5℃ to 5℃.

[0019] The titanium alloy formwork unit serves as the load-bearing foundation, and its working surface forms a composite antifreeze medium layer through a multi-coating process or prefabricated membrane bonding. This composite antifreeze medium layer is tightly bonded from the inside out. The bottom anti-corrosion coating isolates corrosive media and prevents electrochemical corrosion of the titanium alloy substrate in low-temperature and high-humidity environments. The middle phase change heat storage layer encapsulates a material that undergoes solid-liquid or liquid-solid phase transitions within a specific temperature range, serving as the core heat regulation medium. The surface anti-adhesion interface layer has low surface energy characteristics, acting as a barrier to directly contact the concrete to reduce adhesion.

[0020] For example, the composite antifreeze medium layer can be prepared by first sandblasting and cleaning the working surface of the titanium alloy template unit, then applying the bottom anti-corrosion coating by spraying or electrostatic spraying, and after curing, laying the intermediate phase change heat storage layer by scraping or rolling. Finally, the surface anti-adhesion interface layer material can be sprayed or impregnated on the surface of the intermediate layer and cured. Alternatively, a pre-prepared composite film containing the above three-layer structure can be directly pasted onto the working surface of the titanium alloy template unit using a low-temperature resistant adhesive.

[0021] The phase change temperature range is set from -5℃ to 5℃ to maintain a relatively stable temperature at the formwork-concrete interface using the latent heat of phase change. When the ambient temperature fluctuates, the intermediate phase change heat storage layer melts and absorbs heat when the temperature rises due to the heat released during concrete hydration, and solidifies and releases heat when the interface temperature drops due to a decrease in ambient temperature, thus locking the interface temperature within a safe range to prevent the concrete from freezing. This step, through surface modification treatment, endows the titanium alloy formwork with intelligent temperature control and easy demolding properties, laying the material foundation for subsequent low-temperature pouring and rapid demolding.

[0022] Step S2: Template assembly: Refer to Figure 3 The pre-treated titanium alloy template units are assembled using a quick-release connection mechanism. The quick-release connection mechanism includes an elastic locking component and a positioning guide component located on the side of the template unit. The elastic locking component maintains its elastic deformation capability at low temperatures, and the positioning guide component guides adjacent template units to complete the alignment and insertion at ambient temperatures ranging from -20℃ to 0℃.

[0023] The quick-release connection mechanism includes components such as metal locks, positioning pins, and guide sleeves installed on the edge of the template. The elastic locking assembly is made of a material that does not undergo severe embrittlement or significant decrease in elastic modulus at low temperatures, and is used to apply locking force and maintain the connection. The positioning guide assembly is responsible for providing physical constraints and path guidance during the splicing process to ensure tight joints between adjacent template units.

[0024] During assembly, the operator brings two titanium alloy template units close together, aligning the positioning components (such as positioning pins) with the mating components (such as positioning holes). Guided by the positioning guide assembly, the templates are pushed until they are fully fitted. Then, the handle of the elastic locking assembly is turned or rotated to engage its locking mechanism, achieving a fixed connection. For large template units, auxiliary hoisting equipment can be used. The conical self-locking structure of the positioning guide assembly automatically completes the alignment during the template's descent, after which the elastic locking assembly can be manually tightened.

[0025] The positioning and guiding components eliminate misalignment between adjacent template units in the horizontal or vertical directions through physical geometric constraints, ensuring precise alignment and insertion even when operators wear heavy cold-weather gloves, thanks to the mechanical guiding structure, in ambient temperatures ranging from -20°C to 0°C. The elastic locking components maintain sufficient elastic deformation capacity at low temperatures, ensuring adequate locking force and smooth unlocking, preventing jamming or breakage due to low-temperature brittleness. This step, through mechanical structural optimization, overcomes operational obstacles in low temperatures, ensuring the overall rigidity and splicing accuracy of the template system, and providing a closed and stable mold space for concrete pouring.

[0026] Step S3: Freeze Protection: Refer to Figure 2 After the formwork is assembled and before the concrete is poured, circulating hot air is supplied to the back of the formwork to keep the temperature of the formwork working surface between 5°C and 15°C. After the concrete is poured, the phase change heat storage layer absorbs and stores heat under the action of concrete hydration heat, and releases heat when the ambient temperature is lower than the phase change temperature to slow down the cooling rate of the formwork-concrete interface.

[0027] After the formwork assembly is completed and before concrete pouring, hot air at a temperature of 30℃ to 50℃ is delivered to the back of the formwork at a wind speed of 2m / s to 5m / s by arranging flexible air ducts or setting up a hot air jacket. The hot air transfers heat to the titanium alloy formwork through convection heat transfer, thereby heating the working surface until its temperature stabilizes between 5℃ and 15℃. Alternatively, a closed insulated shed can be built outside the formwork, and a hot air blower can be used to heat the air as a whole, allowing the hot air to circulate on the inner and outer surfaces of the formwork to raise the temperature of the working surface. This process aims to eliminate the cold absorption effect of the formwork, prevent the concrete from losing heat too quickly after contacting the low-temperature formwork, and provide a suitable temperature environment for the early hydration reaction of the concrete.

[0028] After concrete pouring, the cement undergoes a hydration reaction, releasing heat. When the interface temperature rises to the phase change point, the phase change material within the phase change heat storage layer undergoes a physical state change (e.g., from solid to liquid), absorbing a large amount of hydration heat and storing it as latent heat. When the external ambient temperature drops, causing the interface temperature to fall to the solidification point of the phase change material, the material undergoes a reverse phase change (e.g., from liquid to solid), releasing the stored heat. In this active preheating + passive heat storage mechanism, the phase change heat storage layer absorbs hydration heat to reduce peak temperatures and prevent temperature cracks. Furthermore, it releases heat when the environment cools, slowing the cooling rate and preventing frost damage to the concrete due to sudden temperature drops, thus ensuring continuous strength growth.

[0029] Step S4: Quick demolding: When the concrete strength reaches more than 50% of the design strength, release the locking of the elastic locking components and remove each titanium alloy formwork unit in sequence. The remaining concrete debris on the working surface of the demolded formwork is cleaned by mechanical vibration.

[0030] When the concrete strength reaches more than 50% of the design strength, it indicates that the concrete has sufficient self-supporting capacity and surface hardness. At this point, the operator uses a special tool to activate the unlocking mechanism of the elastic locking assembly, causing the spring to reset or the locking hook to disengage, thus releasing the connection constraint between adjacent formwork units. Subsequently, a pry bar or suction cup tool is used to separate the formwork from the concrete surface, and each titanium alloy formwork unit is removed in sequence.

[0031] For the dismantled formwork, a handheld high-frequency vibrator can be used to vibrate the formwork surface. The high-frequency vibration force will break the bond between the concrete debris and the surface anti-adhesion interface layer, causing the debris to fall off. Alternatively, the formwork can be placed on a special vibration cleaning platform, and the platform vibrator can be started to vibrate and clean the formwork as a whole. High-pressure air can be used to blow away any remaining debris.

[0032] Setting the demolding strength threshold to over 50% of the design strength utilizes the excellent curing conditions provided by the titanium alloy formwork and composite antifreeze layer, overcoming the limitation of traditional processes that require waiting for the strength to reach over 70%, significantly shortening the construction period and improving formwork turnover efficiency. Mechanical vibration cleaning utilizes the synergistic effect of vibration energy and the low surface energy interface layer to quickly and thoroughly remove concrete debris, solving the problem of low efficiency in manual cleaning and preparing for the next cycle of formwork use.

[0033] The aforementioned technical process combines the high strength and toughness of titanium alloy formwork units with the temperature control characteristics of the composite antifreeze medium layer to construct a thermal protection barrier at the formwork-concrete interface that can both actively preheat and passively regulate temperature. The quick-release connection mechanism utilizes its low-temperature adaptability and guiding positioning function to ensure rapid and precise assembly and disassembly of the formwork system in frigid environments. Active heating by circulating hot air before pouring eliminates the cold bridging effect of the formwork, while the phase change heat storage layer uses hydration heat energy to compensate for heat loss during environmental cooling. Together, these two components smooth out interface temperature fluctuations and prevent concrete from freezing. Combined with the mechanical vibration cleaning mechanism of the low surface energy interface layer, efficient connection between formwork removal and cleaning processes is achieved, comprehensively solving the technical challenges of frost damage, difficult assembly and disassembly, long construction periods, and slow cleaning in concrete construction under low-temperature environments.

[0034] Example 2: In another optional embodiment, the titanium alloy template unit is made of TC4 titanium alloy or TA7 titanium alloy sheet with a thickness of 4mm-10mm. The back of the template unit is provided with crisscrossing reinforcing ribs, which are integrally formed with the template unit, and the cross-section of the reinforcing ribs is T-shaped or L-shaped.

[0035] The material selection for titanium alloy formwork units is based on the specific requirements for material mechanical properties under low-temperature environments. TC4 titanium alloy (Ti-6Al-4V) and TA7 titanium alloy (Ti-5Al-2.5Sn) belong to the α+β type and α type titanium alloys, respectively, exhibiting excellent strength and plasticity matching characteristics under low-temperature conditions. Specifically, TC4 titanium alloy maintains a tensile strength above 1200MPa and an elongation of no less than 10% at -20℃, effectively resisting the risk of low-temperature brittle fracture; TA7 titanium alloy possesses superior microstructural stability and is suitable for extremely cold conditions down to -30℃. Compared to the ductile-brittle transition that easily occurs in ordinary steel at low temperatures, these two titanium alloy materials ensure the structural integrity and reliability of the formwork units during low-temperature handling, assembly, and vibration cleaning processes.

[0036] The thickness of the formwork panels is set at 4mm-10mm to balance the strength and stiffness required for the lateral pressure of concrete pouring with the feasibility of manual handling. Within this thickness range, the self-weight of a single standard-sized formwork unit (e.g., 1200mm×2400mm) can be controlled at around 25kg. This weight design fully considers the operating scenarios where construction workers need to wear heavy protective gear in low-temperature environments, ensuring the convenience and safety of on-site operations.

[0037] The crisscrossing reinforcing ribs on the back of the formwork unit are primarily used to enhance bending stiffness and planar stability, preventing deformation or deflection exceeding allowable values ​​due to excessive lateral pressure during concrete pouring. The grid layout of the reinforcing ribs effectively transfers the uniformly distributed load borne by the panel to the surrounding support system, achieving force dispersion and balanced distribution. The reinforcing ribs are designed with T- or L-shaped sections; compared to traditional rectangular sections, irregularly shaped sections have a higher moment of inertia. While providing the same bending stiffness, this design helps reduce material usage and the self-weight of the formwork unit, thereby achieving lightweight structural optimization.

[0038] The reinforcing ribs and template units are manufactured using an integral molding process, such as integral forging or precision casting, resulting in a continuous transition in microstructure between the reinforcing ribs and the panel, eliminating weld seams or mechanical connection interfaces. This integrated structure avoids the performance inhomogeneity caused by the heat-affected zone of welding and eliminates the risk of fatigue cracks or brittle fractures at the connection interface under repeated low-temperature loading, significantly improving the overall structural safety and service life of the template under harsh low-temperature conditions.

[0039] Example 3: In another optional embodiment, the phase change heat storage layer is a paraffin-based phase change microcapsule coating or an inorganic salt hydrate phase change material coating, with a latent heat of phase change of 150 kJ / kg-250 kJ / kg and a coating thickness of 0.5 mm-2 mm.

[0040] As the core functional unit in the composite antifreeze medium layer, the phase change heat storage layer's material selection and parameter configuration directly determine the template system's thermal buffering capacity and durability in low-temperature environments. This phase change heat storage layer is not a simple accumulation of phase change materials, but rather a functional coating that can be directly applied to the template surface through specific microencapsulation technology or inorganic material formulations.

[0041] Paraffin-based phase change microcapsule coatings are formed by dispersing micron-sized capsule particles, consisting of paraffin-based organic materials as the core and polymers as the shell, within a film-forming matrix. The introduction of microcapsule technology physically alters the morphology of phase change materials. The tiny capsule structures, typically between 10 μm and 100 μm in diameter, possess a vast specific surface area, significantly increasing the heat exchange contact area between the phase change material and the external environment, thereby greatly enhancing the response rate of heat absorption and release. Simultaneously, the capsule shell acts as a physical constraint during the solid-liquid transition of the phase change core material, effectively inhibiting the flow, migration, and leakage of liquid paraffin, ensuring the structural integrity and stability of the coating during repeated freeze-thaw cycles.

[0042] For inorganic salt hydrate phase change material coatings, they are typically prepared by combining inorganic salts such as calcium chloride hexahydrate or disodium hydrogen phosphate dodecahydrate with a film-forming agent. Compared to organic phase change materials, inorganic salt hydrates have higher thermal conductivity and latent heat density of phase change, enabling them to store more heat in the same volume space. This is particularly suitable for thick concrete structures with high heat storage capacity requirements.

[0043] The limitations on latent heat of phase change and coating thickness are the result of multi-dimensional coupling optimization based on the heat release law of concrete hydration and the requirements of low-temperature curing. The latent heat of phase change is set between 150 kJ / kg and 250 kJ / kg. This range characterizes the threshold of heat absorbed or released per unit mass of phase change material during phase change. If the latent heat is below 150 kJ / kg, the heat storage capacity per unit mass of the material is insufficient, and it cannot provide enough heat to resist the invasion of environmental cold sources; if the latent heat is above 250 kJ / kg, it often corresponds to a specific inorganic material system, whose chemical stability or phase change supercooling may be difficult to control.

[0044] The coating thickness setting of 0.5mm-2mm is crucial to the heat conduction path and heat capacity configuration within the coating. While a thinner coating (e.g., 0.5mm) has lower thermal resistance, facilitating rapid response to temperature changes, its total heat storage capacity is limited, making it difficult to sustain a prolonged heat release process. Conversely, a thicker coating (e.g., 2mm) has a larger total heat storage capacity, but excessive thermal resistance hinders heat conduction from the concrete side to the interior of the coating, preventing timely absorption of hydration heat and causing overheating of the concrete surface, or hindering timely heat dissipation when ambient temperature drops sharply. By controlling the latent heat of phase change and coating thickness within the aforementioned range, this embodiment of the application establishes a thermal regulation mechanism that enables rapid heat absorption and stable heat release. This allows for efficient heat absorption and storage during the critical 6-24 hour window of concrete hydration heat release, and continuous heat release to slow the cooling rate of the formwork-concrete interface when ambient temperature decreases.

[0045] Example 4: In one optional embodiment, the elastic locking assembly includes a locking seat disposed on one side of a template unit, a locking hook disposed on the opposite side of an adjacent template unit, and a shape memory alloy spring element located between the locking seat and the locking hook. The shape memory alloy spring element has a modulus of elasticity change rate of no more than 15% at an ambient temperature of -20°C to 0°C.

[0046] The locking seat is fixedly installed on one side edge of the titanium alloy template unit, serving as the fixed end bearing component of the connecting mechanism. It has internal slots or shaft holes for positioning and installing the shape memory alloy spring element. The locking hook is movably installed on the opposite side edge of adjacent titanium alloy template units, serving as the moving end component of the connecting mechanism. Its configuration is such that it retracts under pressure and extends upon reset, forming an interlocking structure with the locking seat. The shape memory alloy spring element is located between the locking seat and the locking hook. As the core elastic energy storage and force application component of the elastic locking assembly, its mechanical properties directly determine the locking force stability and unlocking convenience of the locking assembly in low-temperature environments.

[0047] The shape memory alloy spring element is made of NiTi-based shape memory alloy material. As a functional metallic material with thermoelastic martensitic phase transformation properties, it differs from ordinary spring steel in that it provides restoring force solely based on lattice elastic deformation. Based on the temperature range requirements of low-temperature construction environments (-20℃ to 0℃), NiTi-5%Fe or NiTi-10%Cu alloy wires are selected as raw materials. During the material preparation stage, solution treatment is performed in the temperature range of 800℃ to 1000℃, followed by aging treatment at 300℃ to 500℃ to precipitate strengthening phases and adjust the martensitic phase transformation temperature point, thus adjusting the martensitic phase transformation initiation temperature (M) of the alloy material. x The temperature is controlled below -30℃. Through cold drawing, medium-temperature setting, and post-setting constraint training, the aforementioned wire is processed and shaped into a compression spring or tension spring with specific geometric parameters (wire diameter, mean diameter, number of turns), forming the final shape memory alloy spring element. This element contains a specific crystal microstructure and predetermined geometric dimensions, designed to maintain the austenitic parent phase state within the construction environment temperature range of -20℃ to 0℃, avoiding drastic nonlinear changes in the elastic modulus due to martensitic phase transformation.

[0048] In a low-temperature environment ranging from -20℃ to 0℃, the elastic modulus change rate of the shape memory alloy spring element does not exceed 15%. This technical indicator characterizes the stability of the material's ability to resist elastic deformation at low temperatures; that is, the fluctuation range of the elastic modulus at -20℃ compared to that at 0℃ is strictly limited to within 15%. Compared to the significant hardening phenomenon of conventionally used 65Mn spring steel, which exhibits an elastic modulus change rate as high as 30%-40% in the same isothermal range, the shape memory alloy spring element used in this application demonstrates excellent low-temperature mechanical stability. This stable elastic modulus ensures that the locking force provided by the elastic locking assembly at low temperatures is basically the same as that at room temperature, avoiding problems such as difficulty in unlocking due to excessive locking force or loosening of the connection due to insufficient locking force, and ensuring the consistency of the mechanical response of the connection mechanism across the entire temperature range.

[0049] During dynamic execution, when the operator aligns and presses adjacent titanium alloy template units, the locking hook retracts against the elastic force of the shape memory alloy spring element. At this time, the spring element undergoes elastic deformation and stores elastic potential energy. After the locking hook passes the locking position of the locking seat, the shape memory alloy spring element releases the stored elastic potential energy, quickly pushing the locking hook to reset and pop out, completing the self-locking connection of adjacent template units. When it is necessary to remove the template, the operator only needs to pull the locking hook. The shape memory alloy spring element maintains a stable elastic recovery coefficient at low temperatures, enabling unlocking with a force and response speed similar to that at room temperature. This effectively solves the technical problem of difficult unlocking and low disassembly efficiency caused by the dramatic increase in elastic modulus of ordinary spring steel at low temperatures.

[0050] The aforementioned technical process maintains the stability of the mechanical properties of the connectors in low-temperature environments, ensuring the reliability of the titanium alloy formwork unit connections during rapid assembly and disassembly. The structural design and material selection of this elastic locking assembly allow operators to easily perform locking and unlocking actions even while wearing protective gloves, preventing operational stiffness or failure due to low temperatures and achieving efficient, mechanized construction of formwork projects in low-temperature environments.

[0051] Example 5: In another optional embodiment, in step S3, the circulating hot air is delivered by a flexible air duct set on the back of the template. The flexible air duct is arranged along the splicing seam of the template unit, and air outlet holes are distributed on the surface of the air duct, with the air outlet direction facing the back of the template.

[0052] Flexible ducts create an adjustable hot air delivery channel on the back of the formwork. The ducts can be made of materials such as high-temperature resistant polyethylene or polyurethane corrugated flexible hoses. These materials possess excellent low-temperature resistance and flexibility, allowing them to fit snugly against the back of the titanium alloy formwork and conform to its shape, ensuring close contact even in structurally complex areas such as joints, thereby reducing thermal resistance in the heat transfer path. The ducts are arranged along the joints of the formwork units. This arrangement makes full use of the joint space, avoiding excessive duct space occupation that could affect the subsequent laying of the insulation layer, while ensuring that the hot air source directly covers the joint area where thermal bridging is most pronounced. Air outlets are distributed on the surface of the ducts. The opening parameters of these outlets are crucial for the uniformity of hot air distribution; the hole diameter can be set to, for example, 3mm-8mm, and the hole spacing can be set to, for example, 100mm-300mm. The air outlet is directed towards the back of the template, allowing the hot airflow from the outlet to directly impact the metal surface of the template. This disrupts the laminar boundary layer at the wall-mounted surface, creating a highly turbulent jet that significantly improves the convective heat transfer coefficient, enabling heat to quickly penetrate the titanium alloy template and reach the working surface. This arrangement of openings and the direction of the jet ensures a uniform temperature field on the back of the template, preventing uneven heating caused by localized dead zones in the airflow.

[0053] In step S3, the hot air temperature is 30℃-50℃.

[0054] The setting of the hot air temperature needs to strike a balance between preheating efficiency and the safety of the formwork structure. When the temperature is below 30℃, the temperature difference driving force between the hot air and the low-temperature formwork is insufficient, making it difficult to raise the temperature of the formwork working surface to the target range of 5℃-15℃ within the specified pre-pouring preparation time, resulting in low preheating efficiency. When the temperature is above 50℃, although the heating rate is faster, the excessive temperature difference will cause large thermal stress on the surface of the titanium alloy formwork, posing a risk of thermal deformation of the formwork and also resulting in energy waste. Therefore, the hot air temperature is limited to the preferred window of 30℃-50℃. In actual operation, the hot air temperature can be controlled by adjusting the power of the air heater or the mixing ratio of hot and cold air, while in conjunction with a temperature sensor installed on the back of the formwork for real-time monitoring and feedback adjustment to ensure that the hot air parameters are always under control.

[0055] In step S3, the wind speed is 2m / s-5m / s.

[0056] Wind speed is another key parameter affecting the intensity of convective heat transfer. Within the aforementioned temperature range, controlling the wind speed between 2 m / s and 5 m / s ensures sufficient airflow to remove the cold air behind the template and transfer heat to it, while avoiding excessive airflow noise or severe vibration of the flexible ductwork due to excessive wind speed. When the wind speed is below 2 m / s, the airflow tends to be laminar, resulting in a low heat transfer coefficient and insufficient heat exchange efficiency to meet the requirements of rapid preheating. When the wind speed is above 5 m / s, although the heat transfer coefficient continues to increase, the power consumption of the fan increases cubically, and excessively high wind speeds can easily cause the ductwork to sway and shift behind the template, and may even damage the sealing structure at the joints due to wind pressure fluctuations. By maintaining the wind speed within the range of 2 m / s to 5 m / s, this application can achieve efficient energy transfer and stable airflow control while ensuring uniform coverage of the back of the template with hot air.

[0057] The aforementioned technical features, by defining the arrangement of flexible ducts, the shape of air outlets, and the temperature and velocity parameters of hot air, collectively construct an efficient and controllable active heating environment for the back of the formwork. The precise arrangement of the flexible ducts along the splicing seams and the directional airflow towards the back of the formwork ensure that heat is accurately transferred to the areas most in need; while the combination of hot air temperature of 30℃-50℃ and wind speed of 2m / s-5m / s optimizes the efficiency and safety of the convective heat transfer process, enabling the formwork working surface to reach the temperature conditions required for antifreeze curing in a short time, while avoiding local overheating or energy waste, providing a solid thermal environment foundation for antifreeze curing during subsequent concrete pouring and hydration processes.

[0058] Example 6: In another optional embodiment, the method further includes: laying an insulation layer on the back of the template, the insulation layer being a closed-cell foam board or aerogel felt with a thermal conductivity not exceeding 0.035 W / (m·K), forming an air gap with a thickness of 10 mm to 30 mm between the insulation layer and the back of the template, and circulating hot air flowing in the air gap.

[0059] In the anti-freeze curing stage of step S3, an insulation layer is added to the back of the template to further improve thermal efficiency and reduce heat loss. This insulation layer uses high-performance insulation materials such as closed-cell foam board or aerogel felt. For example, the closed-cell foam board can be extruded polystyrene board (XPS), which has a large number of closed-cell structures, typically with a closed-cell rate of over 95%. This structure effectively blocks moisture penetration and heat convection, maintaining stable low thermal conductivity in low-temperature and humid environments. Aerogel felt is a flexible felt-like material made of nano-sized silica aerogel as the core material, supplemented by a fiber substrate. It has extremely high porosity, with internal pores mainly at the nanoscale, effectively restricting the free movement of air molecules and greatly reducing solid-state heat conduction. Its thermal conductivity at room temperature can be as low as 0.015 W / (m·K) to 0.020 W / (m·K), far superior to traditional insulation materials. Regardless of the material used, the thermal conductivity of the selected insulation layer is controlled to be no more than 0.035 W / (m·K) to ensure sufficient thermal resistance within a limited thickness. During installation, the insulation layer is tightly laid on the outside of the reinforcing ribs of the titanium alloy formwork unit, covering the entire back area of ​​the formwork, forming a major thermal barrier to prevent hot air from diffusing into the external environment.

[0060] When laying the insulation layer, it is not directly attached to the back of the template. Instead, a space of a specific thickness is reserved between the insulation layer and the back of the template through support components or fixing structures, thus forming an air gap. The thickness of this air gap is designed to be 10mm-30mm. The air gap serves a dual key function: on the one hand, as a flow channel for circulating hot air, the hot air from the flexible duct is confined within this space, preventing the hot air from being directly exposed to the external low-temperature environment, allowing heat to be transferred more concentratedly and evenly through the titanium alloy template surface to the working surface; on the other hand, the air gap itself is also an effective thermal insulation structure. When the air in the gap is in a relatively static or low-speed flow state, its thermal conductivity is much lower than that of solid materials (for example, the thermal conductivity of still air is about 0.024W / (m·K)), creating an additional thermal resistance layer between the insulation layer and the metal surface of the template. A thickness range of 10mm-30mm is the preferred value verified by engineering practice: if the thickness is less than 10mm, the wind resistance is too high and it is difficult to form an effective uniform airflow, which can easily cause local overheating or insufficient heat exchange; if the thickness exceeds 30mm, although the insulation layer thickness is increased, it will significantly increase the overall thickness and weight of the formwork system, and the benefit of improving thermal resistance gradually decreases. Within this thickness range, the air jacket and the external closed-cell foam board or aerogel felt together form a composite insulation structure. This structure can produce a synergistic insulation effect, which increases the thermal resistance of the overall insulation system by 30% to 50% compared to a single insulation layer. Thus, with the same amount of heat energy consumed, it significantly extends the constant temperature maintenance time of the formwork working surface, ensuring that the temperature of the concrete-formwork interface can be maintained within the range required for antifreeze in low-temperature environments.

[0061] Example 7: In one optional embodiment, the mechanical vibration cleaning in step S4 uses a high-frequency vibrator with a vibration frequency of 50Hz-200Hz, an amplitude of 0.5mm-2mm, and a vibration time of 10s-60s.

[0062] The high-frequency vibrator, as the core actuator for breaking the frozen bond layer between concrete debris and the formwork working surface in low-temperature environments, essentially converts electrical energy into mechanical energy of a specific frequency and amplitude, and then transmits it to the titanium alloy formwork substrate through contact. The device typically includes a drive motor, an eccentric block assembly, and transmission connectors. The drive motor drives the eccentric block to rotate at high speed, generating centrifugal force, which in turn induces periodic mechanical vibration. The speed of the drive motor directly determines the vibration frequency, while the mass and eccentricity of the eccentric block determine the amplitude. The output end of the device must be reliably connected to the back or side of the titanium alloy formwork unit to ensure that the vibration energy is efficiently transmitted to the working surface and to avoid excessive attenuation during the transmission path.

[0063] The strict limitation of the vibration frequency to 50Hz-200Hz is based on a comprehensive consideration of the acoustic properties of titanium alloy materials and the failure mechanism of the frozen bonding layer. When the vibration frequency is below 50Hz, the generated frequencies are mostly low-frequency displacements, with energy mainly concentrated in rigid body motion, making it difficult to break the bonding bonds between ice crystals and the coating at the microscopic level, resulting in poor cleaning effect. When the frequency is above 200Hz, although the energy density increases, it may induce resonant fatigue in the internal structure of the titanium alloy template, and even lead to the generation of microcracks. In this embodiment, the vibration frequency can be, for example, 50Hz, 80Hz, 100Hz, 120Hz, 150Hz, or 200Hz. In particular, when the frequency is set at around 120Hz, the vibration wave has a high propagation efficiency in the titanium alloy medium, which can effectively form shear stress at the frozen interface, causing fatigue fracture between the concrete debris and the frozen layer on the template surface.

[0064] The amplitude is set between 0.5mm and 2mm. This parameter determines the amount of displacement transmitted by the vibration wave, which directly affects the intensity of the cleaning action. A smaller amplitude (e.g., 0.5mm) produces a smaller displacement and a weaker impact on the template, suitable for mild freezing or coatings that are sensitive to mechanical impact. A larger amplitude (e.g., 2mm) provides stronger peeling force, suitable for thicker concrete residue or deeper freezing conditions. In this embodiment, the amplitude can be, for example, 0.5mm, 1.0mm, 1.5mm, or 2.0mm. By adjusting the amplitude, the most suitable mechanical action intensity can be matched according to the actual cleaning needs, ensuring the cleaning effect while avoiding physical damage to the titanium alloy template or its composite antifreeze layer.

[0065] The vibration time is controlled between 10s and 60s. This time limit defines the duration of a single cleaning operation and is a key parameter for balancing cleaning efficiency and equipment energy consumption. If the vibration time is too short (less than 10s), the vibration energy may not be sufficient to completely destroy all frozen bonding points, resulting in incomplete cleaning. If the vibration time is too long (more than 60s), excessive vibration may cause cumulative damage to the template structure and unnecessarily increase energy consumption and time costs. In this embodiment, the vibration time can be, for example, 10s, 20s, 30s, 40s, 50s, or 60s. For example, for lightly frozen residue, the vibration time can be set to 10s-20s; for heavily frozen residue, the vibration time can be extended to 40s-60s.

[0066] During mechanical vibration cleaning, vibrational energy at specific frequencies and amplitudes is applied to the titanium alloy formwork unit using a high-frequency vibrator. This high-frequency mechanical energy propagates within the titanium alloy formwork, generating rapid reciprocating elastic deformation. When this deformation is transmitted to the working surface of the formwork, it applies periodic inertial and shear forces to the concrete debris adhering to it. Because the concrete debris is bonded to the formwork surface through an ice crystal layer, which exhibits brittle characteristics under high-frequency vibration, it is highly susceptible to fatigue failure under repeated tensile, compressive, and shear stresses. Combined with the low surface energy characteristics of the surface anti-adhesion interface layer (such as a polytetrafluoroethylene coating), the concrete debris rapidly peels off from the formwork surface after the freezing adhesion fails, thus achieving rapid cleaning. By controlling the synergistic effect of vibration frequency, amplitude, and time, this embodiment can efficiently remove residual concrete debris from the working surface of the formwork without manual scraping or water flushing, while ensuring the surface smoothness and coating integrity of the formwork, allowing the formwork to directly proceed to the next construction cycle.

[0067] Example 8: In one optional embodiment, the quick-release connection mechanism further includes a sealing strip disposed at the splice seam of the template unit. The sealing strip is made of silicone rubber or fluororubber and has a hollow cavity inside. The hollow cavity is filled with low-freezing-point antifreeze, and the freezing point of the low-freezing-point antifreeze is not higher than -30°C.

[0068] This sealing strip, a key sealing component in the quick-release connection mechanism, is positioned at the joints of adjacent titanium alloy formwork units. The sealing strip is made of silicone rubber or fluororubber, utilizing the excellent high and low temperature resistance and aging resistance of these materials to ensure long-term elasticity in low-temperature construction environments ranging from -20℃ to 0℃. Silicone rubber typically has a glass transition temperature below -60℃, while fluororubber possesses excellent resistance to chemical corrosion. Both can withstand the low temperatures and alkaline environment of winter construction sites, preventing the sealing strip from becoming brittle and breaking during repeated disassembly and reassembly.

[0069] To further enhance the sealing strip's environmental adaptability in extreme low temperatures, a hollow cavity is incorporated within the strip along its length. This hollow cavity serves as a pressure regulation and deformation buffer space, and is filled with low-freezing-point antifreeze during the prefabrication and assembly stage of the formwork. By controlling the freezing point of the antifreeze to below -30°C, it ensures that the antifreeze remains in a liquid state without freezing within the construction ambient temperature range of -20°C to 0°C. Specifically, a 50%-60% volume concentration of ethylene glycol or propylene glycol antifreeze can be used, as these solutions maintain good fluidity even at -30°C.

[0070] The low-freezing-point antifreeze inside the hollow cavity of the sealing strip, together with the rubber matrix, forms a fluid-solid composite sealing structure. During the assembly of the formwork, when adjacent formwork units are squeezed together by the quick-release connection mechanism, the sealing strip is radially compressed, causing the volume of the hollow cavity to decrease. The internal low-freezing-point antifreeze generates hydraulic support force due to the pressure. Based on the incompressibility of liquids, this reaction force allows the sealing strip to generate a greater contact pressure than ordinary solid rubber strips when under pressure, thereby actively filling the microscopic gaps at the formwork joints, forming a dense physical barrier, and effectively preventing the leakage of cement slurry during concrete pouring.

[0071] To address the issue of conventional solid rubber sealing strips failing to seal in low-temperature environments due to increased material hardness and decreased resilience, this embodiment utilizes a consistently liquid, low-freezing-point antifreeze. This antifreeze redistributes internal pressure to adapt to external compression deformation, compensating for the loss of deformation capacity caused by the increased elastic modulus of the rubber matrix at low temperatures, thus maintaining stable sealing performance. Furthermore, when subjected to thermal expansion and contraction displacement of the template due to temperature changes, the sealing strip absorbs the displacement using the fluidity of the liquid and the volume change of the cavity, preventing permanent deformation due to excessive compression or gaps caused by shrinkage, ensuring long-term sealing reliability under low-temperature conditions.

[0072] Example 9: In another embodiment, the bottom anti-corrosion coating in step S1 is an epoxy zinc-rich coating or a polyurethane coating with a thickness of 20μm-80μm; the surface anti-adhesion interface layer is a polytetrafluoroethylene coating or a diamond-like carbon coating with a thickness of 10μm-50μm.

[0073] The underlying anti-corrosion coating serves as the first barrier between the titanium alloy template substrate and the external environment, playing a crucial role in inhibiting electrochemical corrosion in low-temperature, humid, and highly alkaline concrete environments. This coating is not merely a physical isolation layer, but rather ensures the long-term stability of the template substrate through the synergistic effect of an electrochemical protection mechanism and a highly cross-linked density structure.

[0074] When using an epoxy zinc-rich coating, the coating uses epoxy resin as the film-forming material and is filled with a high proportion of zinc powder. The formation process includes: sandblasting the working surface of the titanium alloy template to Sa2.5 grade; then, uniformly spraying a two-component epoxy zinc-rich primer onto the working surface using an airless spraying device, controlling the spraying pressure and gun speed to form a continuous paint film with a thickness of 20μm-80μm. During the curing process, the epoxy resin cross-links to form a dense network structure, tightly encapsulating and insulating the zinc powder particles, while some zinc powder contacts the titanium alloy substrate through the micropores of the paint film. When the coating surface is scratched or contains trace amounts of moisture or electrolytes, the zinc powder, acting as the anode, preferentially dissolves, releasing electrons that flow to the titanium alloy substrate (cathode). The resulting current polarizes the titanium alloy surface to a negative potential region, thereby inhibiting the oxidation reaction of the titanium alloy. This cathodic protection mechanism ensures that even with minor defects in the coating, the titanium alloy substrate remains free from corrosion. In addition, the thickness range of 20μm-80μm is determined based on the balance between critical film thickness and adhesion: below 20μm, the pinhole rate of the paint film increases and the shielding effectiveness is insufficient; above 80μm, the internal stress of the paint film increases, and cracking and peeling are prone to occur when shrinking at low temperature.

[0075] When polyurethane coatings are chosen as the base anti-corrosion coating, their core advantages lie in their excellent low-temperature flexibility and resistance to chemical corrosion. The coating is constructed by mixing a polyisocyanate prepolymer with a hydroxyl-containing polyester / polyether resin, adding leveling agents and defoamers, and applying it via air spraying or roller coating in a low-temperature environment. The soft segments (such as polyether-type) in the polyurethane macromolecular chain maintain good chain mobility even at ambient temperatures ranging from -20°C to 0°C, giving the coating excellent low-temperature impact resistance, making it less prone to cracking when the template is subjected to mechanical impact or handling. Simultaneously, the high density of urethane bonds (-NHCOO-) in the polyurethane coating molecular structure has strong polarity, forming a strong chemical adsorption and physical anchoring with the titanium alloy substrate, ensuring the adhesion stability of the coating during freeze-thaw cycles.

[0076] The surface anti-adhesion interface layer, which is in direct contact with the cast-in-place concrete, determines the ease of demolding and the quality of the concrete surface. This layer significantly reduces the physical adhesion and chemical adsorption between the concrete paste and the formwork surface through its extremely low surface energy or ultra-high hardness characteristics.

[0077] When polytetrafluoroethylene (PTFE) coating is selected, it utilizes the extremely high bond energy of the carbon-fluorine bond (CF) and the shielding effect of fluorine atoms on the carbon backbone to form a non-adhesive surface with extremely low surface energy (approximately 18 mN / m). The preparation of the PTFE coating involves a suspension spraying followed by high-temperature sintering. PTFE micropowder is dispersed in an organic solvent and sprayed onto the intermediate phase change heat storage layer, then sintered and melted at approximately 380°C to form a continuous, non-porous film. This extremely low surface energy makes it difficult for fresh concrete slurry to wet and spread on the formwork surface; the contact angle is typically greater than 120°, thus minimizing the physical adhesion between the concrete and the formwork. Actual measurement data shows that the demolding resistance using the PTFE coating can be reduced to below 0.4 MPa, a reduction of more than 80% compared to the 2.5 MPa of ordinary steel formwork. This significantly reduces the lifting difficulty and the risk of edge cracking when demolding large volumes of concrete in low-temperature environments. The thickness setting of 10μm-50μm ensures both the continuity and wear resistance of the film, while avoiding the increase in thermal resistance caused by excessive thickness, which would affect heat transfer.

[0078] When diamond-like carbon (DLC) coatings are selected as the surface anti-adhesion interface layer, their mechanism of action shifts to relying on high hardness and low coefficient of friction to achieve anti-adhesion and wear resistance. DLC coating is an amorphous carbon film containing diamond (sp³ bonds) and graphite (sp² bonds) structures, exhibiting extremely high hardness and elastic modulus. The formation of this coating involves using plasma-enhanced chemical vapor deposition (PECVD) technology, employing hydrocarbon gases (such as methane and acetylene) as precursors, and generating plasma through glow discharge in a vacuum environment to deposit a thin film with a thickness of 10μm-50μm on the template surface. The high hardness of the DLC coating (above HV2000) enables it to resist the scraping and abrasion of coarse aggregates in concrete during pouring and vibration, as well as the micro-cutting action generated by high-frequency vibration during mechanical vibration cleaning, ensuring that the surface roughness (Ra) of the template increases very little after long-term use (e.g., Ra increases by only 0.05μm after 20 seconds of vibration at 120Hz). Meanwhile, the DLC coating has self-lubricating properties and a low coefficient of friction, which further reduces the shear stress at the interface between the concrete and the template during hardening shrinkage. Combined with the flexible transition between the bottom and intermediate layers, it forms a gradient anti-adhesion system that combines soft and hard materials.

[0079] Through the specific configuration of materials and thickness of the aforementioned bottom anti-corrosion coating and the surface anti-adhesion interface layer, and in conjunction with the intermediate phase change heat storage layer of the above embodiment, the composite antifreeze medium layer forms a functionally graded protective system in low-temperature, high-humidity, and highly alkaline concrete construction environments. The high adhesion and electrochemical protection capabilities of the bottom layer ensure that the entire coating system does not experience interlayer delamination or substrate corrosion, while the low surface energy or high wear resistance of the surface layer directly solves the technical problems of concrete sticking to the formwork and difficult cleaning at low temperatures. The synergistic effect of each layer ensures the reliability and durability of the titanium alloy formwork during the winter construction period.

[0080] Example 10: In another embodiment, this application also provides a specific implementation scheme for a positioning and guiding component in a rapid disassembly and assembly process for titanium alloy formwork under low-temperature conditions. In step S2, the positioning and guiding component includes a tapered positioning pin disposed on one side of the formwork unit and tapered positioning holes disposed on opposite sides of adjacent formwork units. A flexible guide sleeve is disposed between the tapered positioning pin and the tapered positioning hole. The change in Shore hardness of the flexible guide sleeve at -20℃ compared to that at room temperature does not exceed 5HA.

[0081] The tapered locating pin and tapered locating hole form the basic framework of the positioning and guiding assembly. A tapered mating structure replaces the traditional cylindrical pin mating, utilizing the geometric characteristics of the tapered surface to achieve automatic alignment between adjacent template units. When there is a relative positional deviation between adjacent template units, the inclined surface of the tapered locating pin generates a lateral force on the tapered locating hole, forcing them to slide relative to each other until they are coaxial during insertion, thereby correcting the initial positional error. In practical engineering applications, the taper of the tapered locating pin can be set, for example, between 5° and 15°. This taper range ensures the guiding and self-locking function while allowing for a certain initial positional deviation between adjacent template units, for example, a deviation of ±5mm, adapting to conditions where the operational flexibility of construction personnel is reduced in low-temperature environments.

[0082] The flexible guide sleeve, serving as a crucial elastic medium between the tapered locating pin and the tapered locating hole, is physically shaped as a tubular bushing wrapped around the surface of the locating pin or an annular gasket embedded within the locating hole. At room temperature, the flexible guide sleeve exhibits high elasticity, absorbing impact loads during the insertion process through its elastic deformation. However, in low-temperature construction environments (e.g., -20°C), ordinary rubber materials harden and become brittle due to molecular chain freezing, leading to guiding failure. The flexible guide sleeve's Shore hardness at -20°C does not exceed a 5HA change compared to room temperature, ensuring the material maintains good flexibility even under extremely cold conditions. This small change in Shore hardness indicates that the material's internal microstructure has not undergone a significant glass transition at low temperatures, and its elastic modulus and yield strength remain within usable ranges. This characteristic allows the flexible guide sleeve to withstand significant compressive deformation (e.g., compression ratios exceeding 40%) at low temperatures without brittle fracture, and it rapidly recovers its original shape after pressure removal, providing continuous friction reduction and guidance for the relative movement of the locating pin and the locating hole.

[0083] In practical implementation, flexible guide sleeves can be made of, for example, low-temperature toughened modified polyurethane elastomers or silicone rubber materials. These materials suppress low-temperature crystallization tendencies by adding specific plasticizers or altering crosslinking density. For example, for silicone rubber guide sleeves, by introducing phenyl groups with large side groups or optimizing the vinyl content, their glass transition temperature (Tg) can be lowered, allowing them to maintain high elasticity even below -40°C. The variation in Shore hardness can be controlled through low-temperature thermal aging tests: samples with a Shore A hardness of 50HA to 70HA at room temperature (23°C) are selected, placed at a constant temperature of -20°C for 24 hours, and their hardness values ​​are tested. Formulas with a hardness increase not exceeding 5HA are selected. This material selection logic ensures that the mechanical property curve of the guide sleeve remains flat within the ambient temperature range of -20°C to 0°C, preventing drastic changes in insertion resistance due to small temperature fluctuations.

[0084] The aforementioned technical features create a close synergistic effect during operation: when the operator closes adjacent titanium alloy template units, the tapered locating pin first inserts into the large end of the tapered locating hole. Due to the guiding effect of the tapered surface, even if there is a slight misalignment between the axes, the tapered locating pin can slide in smoothly. As the insertion depth increases, the tapered locating pin gradually expands the flexible guide sleeve inside the tapered locating hole, causing the flexible guide sleeve to expand radially and fit tightly between the two. At this stage, the flexible guide sleeve utilizes its low hardness characteristic maintained at low temperatures to fill the manufacturing gap between the tapered locating pin and the tapered locating hole, and flexibly corrects the relative positional deviation between the two, transforming rigid contact into flexible contact and avoiding jamming or damage caused by direct collision of metal parts. When the tapered locating pin is fully inserted, the flexible guide sleeve, due to its own elasticity, generates a continuous radial clamping force on the tapered locating pin, achieving stable positioning of adjacent template units and providing a precise positional reference for the subsequent locking of the locking assembly.

[0085] By employing tapered positioning pins and holes in conjunction with a flexible guide sleeve with specific low-temperature performance, the template assembly process in step S2 achieves a balance between high precision and high efficiency in low-temperature environments. The self-aligning function of the tapered structure, combined with the low-temperature adaptability of the flexible guide sleeve, solves the problems of difficult insertion and large positioning deviations caused by inconsistent component shrinkage or hardening of rubber parts in traditional guide mechanisms at low temperatures. This ensures that the titanium alloy template unit can quickly and accurately complete alignment and insertion in ambient temperatures ranging from -20℃ to 0℃, providing a reliable guarantee for subsequent rapid locking and the stability of the overall structure.

[0086] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. A rapid assembly and disassembly process for antifreeze titanium alloy formwork in low-temperature environments, characterized in that, Includes the following steps: S1. Template pretreatment: Provide a titanium alloy template unit. The working surface of the titanium alloy template unit is coated with a composite antifreeze medium layer. The composite antifreeze medium layer consists of a bottom anti-rust coating, an intermediate phase change heat storage layer and a surface anti-adhesion interface layer. The phase change temperature range of the phase change heat storage layer is -5℃ to 5℃. S2, Template Assembly: The pre-treated titanium alloy template units are assembled using a quick-release connection mechanism. The quick-release connection mechanism includes an elastic locking component and a positioning guide component located on the side of the template unit. The elastic locking component maintains its elastic deformation capability at low temperatures, and the positioning guide component guides adjacent template units to complete the alignment and insertion at ambient temperatures ranging from -20℃ to 0℃. S3. Anti-freezing curing: After the formwork is assembled and before the concrete is poured, circulating hot air is delivered to the back of the formwork to keep the working surface temperature of the formwork between 5°C and 15°C. After the concrete is poured, the phase change heat storage layer absorbs and stores heat under the action of concrete hydration heat, and releases heat when the ambient temperature is lower than the phase change temperature to slow down the cooling rate of the formwork-concrete interface. S4. Quick demolding: When the concrete strength reaches more than 50% of the design strength, release the locking of the elastic locking assembly, and remove each titanium alloy formwork unit in sequence. The remaining concrete debris on the working surface of the demolded formwork is cleaned by mechanical vibration.

2. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The titanium alloy template unit is made of TC4 titanium alloy or TA7 titanium alloy sheet with a thickness of 4mm-10mm. The back of the template unit is provided with crisscrossing reinforcing ribs, which are integrally formed with the template unit and have a T-shaped or L-shaped cross section.

3. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The phase change heat storage layer is a paraffin-based phase change microcapsule coating or an inorganic salt hydrate phase change material coating, with a latent heat of phase change of 150kJ / kg-250kJ / kg and a coating thickness of 0.5mm-2mm.

4. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The elastic locking assembly includes a locking seat disposed on one side of the template unit, a locking hook disposed on the opposite side of an adjacent template unit, and a memory alloy spring element located between the locking seat and the locking hook. The elastic modulus change rate of the memory alloy spring element in an ambient temperature range of -20℃ to 0℃ does not exceed 15%.

5. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The circulating hot air in step S3 is delivered by a flexible air duct set on the back of the template. The flexible air duct is arranged along the splicing seam of the template unit, and air outlet holes are distributed on the surface of the air duct. The air outlet direction is towards the back of the template. The hot air temperature is 30℃-50℃ and the air velocity is 2m / s-5m / s.

6. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, Step S3 also includes: laying an insulation layer on the back of the template, wherein the insulation layer is a closed-cell foam board or aerogel felt with a thermal conductivity not exceeding 0.035 W / (m·K), and an air gap with a thickness of 10 mm-30 mm is formed between the insulation layer and the back of the template, wherein the circulating hot air flows in the air gap.

7. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The mechanical vibration cleaning in step S4 uses a high-frequency vibrator with a vibration frequency of 50Hz-200Hz, an amplitude of 0.5mm-2mm, and a vibration time of 10s-60s.

8. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The quick-release connection mechanism also includes a sealing strip set at the splice seam of the template unit. The sealing strip is made of silicone rubber or fluororubber and has a hollow cavity inside. The hollow cavity is filled with low freezing point antifreeze, and the freezing point of the low freezing point antifreeze is not higher than -30°C.

9. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The bottom anti-corrosion coating in step S1 is an epoxy zinc-rich coating or a polyurethane coating with a thickness of 20μm-80μm; the surface anti-adhesion interface layer is a polytetrafluoroethylene coating or a diamond-like carbon coating with a thickness of 10μm-50μm.

10. The antifreeze construction process for titanium alloy formwork that can be quickly assembled and disassembled in low-temperature environments according to claim 1, characterized in that, The positioning guide assembly in step S2 includes a tapered positioning pin disposed on one side of the template unit and a tapered positioning hole disposed on the opposite side of the adjacent template unit. A flexible guide sleeve is disposed between the tapered positioning pin and the tapered positioning hole. The Shore hardness of the flexible guide sleeve at -20℃ changes by no more than 5HA compared with that at room temperature.